Analysis of financing, marketing and profitability of melon with a “sowing by stages” approach in the Comarca Lagunera region of Coahuila state, Mexico - Espinoza-Arellano, José de Jesús (Universidad Autónoma de Tamaulipas, 2019)
The Comarca Lagunera, with a participation of 25 % of the national production, is the most important melon region in the country. Despite its importance, recent studies reflecting its socio-economic situation are lacking. In this work, the objective was to generate information on the issues of financing, commercialization and profitability of melon cultivation with a “step by step” approach, which will serve as the basis to promote the development of this crop in the Coahuila Lagunera Region. To obtain the necessary information, a questionnaire was prepared and administered to 60 melon producers in the study area. The questionnaire was composed of 30 items, divided into five blocks, on the topics of: technical aspects of cultivation, financing, production costs, revenue and marketing. In marketing, three “stages” of planting and harvesting were identified during the year, with “early” and “late” dates being sold at better prices, but with greater climatic and biological risks; while, the “intermediaries” were those with higher production and lower risk, but with lower profitability, when sold at lower prices. The situation regarding financing continues to be a limitation for the profitability of this crop, with expensive and scarce credits. In commercialization, it was found that it continues to depend on intermediaries. It is concluded that it is necessary to reinforce the organization to be able to do a better planning of the sowing and harvesting stages, to obtain more accessible financing and with greater coverage, as well as to strengthen the negotiation capacity with the intermediaries.